Imaging Idiopathic Chylopericardium With 99mTc-SC Lymphoscintigraphy and SPECT/CT. (November 2015) - Atkinson, Chris; Banks, Kevin
<x xml:space="preserve">Abstract</x> Abstract A 27-year-old asymptomatic active duty military man underwent a screening chest x-ray secondary to a history of tuberculosis exposure. His chest x-ray showed no features of tuberculosis infection but unexpectedly revealed a markedly enlarged cardiac silhouette. Echocardiography demonstrated a large pericardial effusion without tamponade physiology. Pericardiocentesis revealed chylous fluid. The effusion was initially refractory to drainage requiring VATS for therapy. Lymphoscintigraphy was performed using 99mTc-SC to evaluate lymphatic anatomy and confirm communication with the pericardial space. Novel use was made of SPECT/CT with the hope of better assessing the nature of the abnormal communication and potentially helping guide management.